Intellectualism in higher Islamic traditional studies: implications for the curriculum - Hashim, Rosnani (Association of Muslim Social Scientists, 2007)
The number of faculties and universities offering Islamic traditional sciences or studies has slowly increased over the past decades. However, the Islamic community has not felt their graduates’ impact other than as teachers or religious personnel. In fact, if the criteria used to assess Islamic education is the growth of a genuine, original, and adequate Islamic thought or intellectualism, then most of these institutions have failed to provide such an education. I examine the goals and curriculum of higher Islamic education and the conditions conducive for the growth of intellectualism. I argue that poor pedagogy, which does not offer teaching methods that encourage critical and ethical thinking, contributed to the state of affairs. Further, I argue that the basic problem is the inadequate conceptualization of knowledge as regards Islamic epistemology in the curriculum and the lack of academic freedom. I assert that the issue of what knowledge is most valuable for today’s intellectual and ethical Muslims has not been resolved and that this affects the curriculum structure and, inevitably, the programs of Islamic traditional sciences. The need to reintroduce Islamic philosophy into the curriculum is one of this article’s major arguments.